Security, risk perception and cost-benefit analysis: Summary and conclusions - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
Security concerns are high on the political agenda in many countries because of the widespread perception that security is increasingly threatened by intentional malicious acts including terrorist attacks. While terrorism has a long history and measures to maintain and improve security are in place, major events - including but not limited to the 9/11 attacks - have triggered stronger action to improve security. In this context, much attention goes to maintaining secure transport for two reasons. First, many transport facilities and vehicles are appealing targets for terrorist attacks because of the concentration of potential victims. Second, transport can act as a conveyor for terrorist attacks, e.g. by moving weapons into ports or by turning airplanes into weapons. In both cases, the difficulties in protecting the many potential targets while maintaining smooth transport operations strengthens the appeal of transport targets.
Keywords: 330